2021
DOI: 10.3389/fdgth.2021.644539
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Design and Implementation of Technologies for Workplace Health Promotion: A Call for Discussion

Abstract: Aim: This study aims to initiate discussion on the ethical issues surrounding the development and implementation of technologies for workplace health promotion. We believe this is a neglected topic and such a complex field of study that we cannot come up with solutions easily or quickly. Therefore, this study is the starting point of a discussion about the ethics of and the need for policies around technologies for workplace health promotion.Method: Based on a literature review, the present study outlines curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…There appears to be considerable scope to provide more technological guidance, and concrete examples of incorporating principles into technology development. Indeed, a growing body of literature offers and reflects on responsible design for digital health research 49 , interventions 50 – 52 , and technology development 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be considerable scope to provide more technological guidance, and concrete examples of incorporating principles into technology development. Indeed, a growing body of literature offers and reflects on responsible design for digital health research 49 , interventions 50 – 52 , and technology development 11 .…”
Section: Discussionmentioning
confidence: 99%
“…and support the patient in managing their health status (e.g., drug alerts, warnings, physical activity alerts, diet suggestions, etc.) This represents the overall "Virtual PHI repository" (17), in which personal data are not limited to those generated when the individual is a "patient" but also when she/he is still healthy. Clinical data in the electronic health record (EHR) are part of personal data managed within healthcare information systems.…”
Section: Technological Considerationsmentioning
confidence: 99%
“…In the long run, the data generated and collected within a pHealth system will be relevant not only at the personal but also at the population level, in the light of "precision public health" (1). This complexity allows the transition from the simple definition of a pHealth digital system to a pHealth "ecosystem" (17), in which the common goal of all stakeholders is the patient. Solving this challenge requires the ontological representation of the business system and its domains involved, and this especially holds for policies and ethical challenges in transformed health ecosystems (41).…”
Section: Technological Considerationsmentioning
confidence: 99%
“…For further studies, we suggest specifying regarding the type of digital intervention and investigating which trainings employees see a need for. As raised by the respondents and in research (Roossien et al, 2021), ethical and privacy issues need to be observed in the design. This is especially relevant in the context of protecting users and their interests (Lupton, 2015).…”
Section: Source(s): Spss Outputmentioning
confidence: 99%
“…Based on the current literature (Kwasnicka et al ., 2022), we define DWHP as the use of digital means and tools to create and deliver health interventions for employees. This includes digital health applications, for example, for smartphones, activity trackers and sensors used for automated feedback on health behaviour (Roossien et al ., 2021), digitally providing health information for employees, using digital platform for all parts of the WHP-cycle, covering need assessment, intervention and evaluation (Walter et al ., 2019), or providing WHP activities as videos (Oppermann and Dierks, 2023), via streaming or as recordings.…”
Section: Introductionmentioning
confidence: 99%